2010
DOI: 10.1038/icb.2009.115
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils and Th2 immunity: contemporary insights

Abstract: Eosinophils, innate immune leukocytes elicited by Th2 cells, have long been associated with the effector arm of Th2 immune responses. However, accumulating data over the past decade reveal a much more dynamic picture of Th2 immunity, where eosinophils are present very early in response to Th2-inducing agents and function in the initiation of Th2 immunity. Here we discuss recent data showing immune functions of eosinophils distinct from their previously appreciated tissue- and helminth-destructive capacities, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(114 citation statements)
references
References 80 publications
6
104
1
Order By: Relevance
“…Eosinophils are also known to contribute to the generation of Th2 immunity. In fact, many studies have shown that eosinophil deficiency inhibits the efficient generation of the Th2 immune response (21,22). In our model, we found that eosinophils were recruited to the vaginal tissues after intravaginal papain immunization (Fig.…”
Section: Basophils and Eosinophils Are Dispensable For The Intravaginalsupporting
confidence: 50%
“…Eosinophils are also known to contribute to the generation of Th2 immunity. In fact, many studies have shown that eosinophil deficiency inhibits the efficient generation of the Th2 immune response (21,22). In our model, we found that eosinophils were recruited to the vaginal tissues after intravaginal papain immunization (Fig.…”
Section: Basophils and Eosinophils Are Dispensable For The Intravaginalsupporting
confidence: 50%
“…Unlike neutrophils that are involved in the antibacterial Th1 reactions, eosinophils are important mediators of Th2 immunity, producing a vast array of Th2 cytokines (e.g. IL4, IL10, IL13, and TGFB) that participate in anti-inflammatory immune responses, M2 polarization of macrophages, and differentiation of Th2 cells (Spencer & Weller 2010).…”
Section: Eosinophilsmentioning
confidence: 99%
“…The eosinophils could not only promote naive CD4 + T cells to differentiate into Th2 cells by secreting cytokines such as IL-4 and IL-13, but they also could present Ags to naive CD4 + T cells directly to promote Th2 polarization. Moreover, chemokines such as eotaxin 1 and CXCL1 secreted by the eosinophils could recruit Th2 effector cells to the infected tissue (29). Based on the understanding that a correct Th1 versus Th2 balance is needed, the various prototype vaccines that have been developed are mainly aimed at inducing a strong Th1-type response and avoiding Th2.…”
mentioning
confidence: 99%